Antioxidants and cardioprotection - Hamilton, K. L. (Medicine & Science in Sports & Exercise, 2007)
Limiting myocardial ischemia-reperfusion (IR) injury is essential for preventing contractile dysfunction and limiting morbidity and mortality associated with ischemic heart disease. Over the last few decades, it has become clear that during IR insults, myocardial oxygen radical formation is accelerated and plays a critical role in mediating cellular damage and dysfunction. This review provides a brief summary of a variety of approaches that have been undertaken to alleviate the oxidant stress associated with myocardial IR, and a summary of the data demonstrating the potential therapeutic value of oxidant scavenging in limiting IR-induced myocardial damage. Included is a review of investigations using novel free radical scavengers, antioxidant extracts from a variety of plants, polyphenolic compounds from foods such as cocoa, soy, grapes, and wine, as well as vitamin E, vitamin C, and [beta]-carotene. Also reviewed is the evidence that exercise-induced increases in endogenous antioxidants may be an important change contributing to cardioprotection. One must conclude from this brief review that current evidence suggests that enhancing oxidant-scavenging capacity protects against some of the cardiomyocyte disturbances during IR and helps salvage myocardial tissue. Data in cultured cell and animal models are convincing; trials in humans are significantly more conflicting, but still promising.